Nouveau traitement de l'équation de Schrödinger pour le nouveau potentiel de Cornell modifié dans l'espace de phase non commutatif à deux dimensions - Abdelouahab, Mohamed. Bahache, Fouad (Université Mohamed BOUDIAF de M'Sila, 2019)
In this work, of master memory, in theoretical physics, (2018/2019), we have studied the Schrödinger equation with new modified Cornell potential by the temperate and the relative distance between quark and antiquark in noncommutative two dimensional spaces and phases by applying the Bopp's shift method to first order in the noncommutative parameters (, ), instead of using the star product method. The corrections of energy levels obtained by applying standard perturbation theory for quarkonium systems, it has been observed that the obtained energy spectra was changed radically, and replaced by degenerate new states, depending on the discrete quantum atomic number m , these results produced from self-Zeeman effect
Keywords: Star product, noncommutative space and phase, Cornell potential